2013
DOI: 10.3791/50522
|View full text |Cite
|
Sign up to set email alerts
|

The <em>In ovo</em> CAM-assay as a Xenograft Model for Sarcoma

Abstract: Citation: Sys, G.M.L., Lapeire, L., Stevens, N., Favoreel, H., Forsyth, R., Bracke, M., De Wever, O. The In ovo CAM-assay as a Xenograft Model for Sarcoma. J. Vis. Exp. (77), e50522, doi:10.3791/50522 (2013). AbstractSarcoma is a very rare disease that is heterogeneous in nature, all hampering the development of new therapies. Sarcoma patients are ideal candidates for personalized medicine after stratification, explaining the current interest in developing a reproducible and low-cost xenotransplant model for t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
45
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(49 citation statements)
references
References 25 publications
2
45
0
Order By: Relevance
“…In previous studies, several osteosarcoma cell lines have been found to form solid tumors on CAMs, with a rich vascular response3637. In this study, to assess the anti-cancer activity of ELH in vivo , we examined the ability of HT1080 cells to form solid tumors on CAMs with or without ELH treatment.…”
Section: Resultsmentioning
confidence: 99%
“…In previous studies, several osteosarcoma cell lines have been found to form solid tumors on CAMs, with a rich vascular response3637. In this study, to assess the anti-cancer activity of ELH in vivo , we examined the ability of HT1080 cells to form solid tumors on CAMs with or without ELH treatment.…”
Section: Resultsmentioning
confidence: 99%
“…These include detailed observations of organ (e.g., eye, brain etc) or tissue development (e.g., blood vessel growth) or application of teratogenic agents. Manipulations include grafting of tissues onto the chorioallantoic membranes to study the effect of combining different tissue layers or studying tumor growth and metastasis 14 .…”
Section: Representative Resultsmentioning
confidence: 99%
“…The mechanism of this transport seems to rely on the sequestration of calcium within endosome-like vesicles upon the initial uptake phase [94]. Interestingly, in vitro CAM ectodermal cells exhibit faster calcium influx rates when compared to human erythrocytes suggesting alternative calcium entry mechanisms [175].…”
Section: Cam As a Screening Platformmentioning
confidence: 99%